Peran Business Intelligence dalam Solusi Bisnis - Siswono, Siswono (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The purpose of this study is to give examine the use of Business Intelligence as a critical technology solutions in the decision making by management. Business Intelligence application is able to address the needs of organizations in improving problem analytical skills encountered in making decisions with the ability tocollect, store, analyze and provide access to data, as well as dovarious activities such as statistical analysis, forecasting, and data mining.